If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + 120 = 2(x + 7)(x + -3) Reorder the terms: 120 + a = 2(x + 7)(x + -3) Reorder the terms: 120 + a = 2(7 + x)(x + -3) Reorder the terms: 120 + a = 2(7 + x)(-3 + x) Multiply (7 + x) * (-3 + x) 120 + a = 2(7(-3 + x) + x(-3 + x)) 120 + a = 2((-3 * 7 + x * 7) + x(-3 + x)) 120 + a = 2((-21 + 7x) + x(-3 + x)) 120 + a = 2(-21 + 7x + (-3 * x + x * x)) 120 + a = 2(-21 + 7x + (-3x + x2)) Combine like terms: 7x + -3x = 4x 120 + a = 2(-21 + 4x + x2) 120 + a = (-21 * 2 + 4x * 2 + x2 * 2) 120 + a = (-42 + 8x + 2x2) Solving 120 + a = -42 + 8x + 2x2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-120' to each side of the equation. 120 + -120 + a = -42 + 8x + -120 + 2x2 Combine like terms: 120 + -120 = 0 0 + a = -42 + 8x + -120 + 2x2 a = -42 + 8x + -120 + 2x2 Reorder the terms: a = -42 + -120 + 8x + 2x2 Combine like terms: -42 + -120 = -162 a = -162 + 8x + 2x2 Simplifying a = -162 + 8x + 2x2
| -5x^2+9x+2=0 | | 5x-2=26-2x | | -18=-2n | | 6(2-t)-(3-4t)=4 | | 5(x+8)=2(x+6) | | 5(x-8)=2(x+6) | | -4=3x | | 2x-18=9x+2 | | 7p-11=-3p+7 | | -(7y+1)-(-6y-6)=-2 | | 4(x+1)+2(x+6)=3 | | 7n+24=32 | | 7n-24=42 | | 3x-45=889 | | 8(3x+7)=2(12x+5) | | 3x-9999= | | 345-23+889x= | | 8+2n-2=8n+6-4n | | 7-24=42 | | 3x-23= | | 2r+18r=140 | | 5x^3-20x^2-5x+20=0 | | -9(2b+1)+(19b-6)=0 | | 4.3q-2.3-3.8q=-0.5q-3.3 | | 5x+10y=8 | | -5y+7=-6y+2 | | (0.288)(1-2x)=4x^3 | | 3x-7-2x^2=0 | | (3x-7)+2x^2=0 | | (X+2)(3x^2-4x+5)=0 | | 3x^2+6x-2+-7x+5=0 | | 5=x^2-3x |